PROBLEMATIC APPROACH IN PEDAGOGICAL PROCESSES - THE BASIS OF ACTIVATION PROFESSIONAL POSITION OF STUDENTS (Pedagogy of Higher and Secondary Education, 2004)
The author determined the essence of active professional position, the structure of responsibility and it’s contents. In the research work the totality of pedagogical conditions providing the efficiency of pedagogical training in the process of formation of active professional position of the future teachers has been proved by the means of experiments.